Detection of Cholesterol in Suaeda Baccata (Chenopodiaceae) - S. Al-Mohammadi, Suhad (Iraqi Journal of Pharmaceutical Sciences, 2017)
This study detects the presence of cholesterol in an Iraqi plant named Suaeda baccata Forsk of the family Chenopodiacae, wildly and widely grown in Iraq. The absence of any publication concerning the sterol content of this Suaeda specie, and the industrial importance of cholesterol depending on its role as a precursor in the synthesis of some hormones, like progesterone, acquired this study its value. The investigations revealed the presence of cholesterol that was proved by TLC together with the standard compound cholesterol, and anisaldehyde spray reagent using three different solvent systems, then authenticated by HPLC, in which the retention time of both the standard cholesterol and the plant extract cholesterol were identical. Key Words: Cholesterol, Suaeda Baccat and Chenopodiaceae